Educational Management Graduates: A Tracer Study from Universitas Negeri Surabaya, Indonesia - Shelly Andari; Aditya Chandra Setiawan; Windasari; Ainur Rifqi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Tracer Study is a study that can provide helpful information to evaluate higher education results and can then be used to improve and guarantee the quality of higher education institutions. This research uses a quantitative research approach with the type of survey research. The research population is graduates of the Educational Management Department who graduated in 2019 and 2020. The sample used is saturated sampling, where the entire population is a member of the sample. The study results were analyzed using descriptive statistics and extracted information about graduates, including the number of graduates. It includes who graduated, graduates employment status, waiting time for graduates, coverage of where graduates work, and other descriptions are required by Badan Akreditasi Nasional Perguruan Tinggi (i.e., BAN-PT). BAN-PT is an accreditation organization in Indonesia, where accreditation and input for curriculum development of Educational Management Department. The result showed that Educational Management graduates could be survived as employees or entrepreneurs that focus on Educational Management scope.